Literatura e compreensão de textos: as dimensões do cotidiano escolar - Silva, Jandaíra Fernandes da (2011)
This dissertation aims to understand why the young do not like reading classical literature and elaborates an approach on the importance of reading for the liberation of human beings. In this way, the author brings back memories of the journey of learning of reading and experience reports as educator. This text was built guided by authors who write about the respective topic. It sought to delineate the peculiarities about some books and teaching practices of the author and colleagues in a funny way, as well as some impressions of students in relation to the proposals of readings. The research methodology was the use of private records collected from observations and experiences, redeemed by memory during the production of this text. With this study, we hope to contribute to the reflections that involve the reading of the literary text, specially the classics, toward the advancing of the process of formation of the literary reader in school. However, it is not intended to present something new with these reflections, but to provoke new perspectives on the issue.